Drug Shortage: Causes, Impact, and Mitigation Strategies - Shukar, Sundus; Zahoor, Fatima; Hayat, Khezar; Saeed, Amna; Gillani, Ali Hassan; Omer, Sumaira; Hu, Shuchen; Babar, Zaheer-Ud-Din; Fang, Yu; Yang, Caijun (Frontiers in Pharmacology, 2021)
Drug shortage is a global issue affecting low, middle, and high-income countries. Many countries have developed various strategies to overcome the problem, while the issue is accelerating affecting the whole world. All types of drugs, such as essential life-saving drugs, oncology medicines, antimicrobial drugs, analgesics, opioids, cardiovascular drugs, radiopharmaceutical, and parenteral products, are liable to the shortage. Among all pharmaceutical dosage forms, sterile injectable products have a higher risk of shortage than other forms. The causes of shortage are multifactorial, including supply issues, demand issues, and regulatory issues. Supply issues consist of manufacturing issues, unavailability of raw materials, logistic issues, and business issues. In contrast, demand issues include just-in-time inventory, higher demand for a product, seasonal demand, and unpredictable demand. For regulatory issues, one important factor is the lack of a unified definition of drug shortage. Drug shortage affects all stakeholders from economic, clinical, and humanistic aspects. WHO established global mitigation strategies from four levels to overcome drug shortages globally. It includes a workaround to tackle the current shortage, operational improvements to reduce the shortage risk and achieve early warning, changes in governmental policies, and education and training of all health professionals about managing shortages.